How should we treat acute kidney injury caused by renal congestion? - Masanori Abe; Seiichiro Hemmi; Hiroki Kobayashi (The Korean Society of Nephrology, 2023)
Decreased kidney function is associated with increased risk of cardiovascular events and mortality, and heart failure (HF) is a well-known risk factor for renal dysfunction. Acute kidney injury (AKI) in patients with HF often is attributed to prerenal factors, such as renal hypoperfusion and ischemia as a result of decreased cardiac output. Another such factor is reduction of absolute or relative circulating blood volume, with the decrease in renal blood flow leading to renal hypoxia followed by a decrease in the glomerular filtration rate. However, renal congestion is increasingly being recognized as a potential cause of AKI in patients with HF. Increased central venous pressure and renal venous pressure lead to increased renal interstitial hydrostatic pressure and a reduction of the glomerular filtration rate. Both decreased kidney function and renal congestion have been shown to be important prognostic factors of HF, and adequate control of congestion is important for improving kidney function. Loop and thiazide diuretics are recommended as standard therapies to reduce volume overload. However, these agents are associated with worsening renal function even though they are effective for improving congestive symptoms. There is growing interest in tolvaptan, which can improve renal congestion by increasing excretion of free water and decreasing the required dose of loop diuretic, thereby improving kidney function. This review summarizes renal hemodynamics, the pathogenesis of AKI due to renal ischemia and renal congestion, and diagnosis and treatment options for renal congestion.